Geometric morphometric analysis of craniofacial variation, ontogeny and modularity in a cross-sectional sample of modern humans. - Wellens, H L L; Kuijpers-Jagtman, A M; Halazonetis, D J (J Anat, 2013)
This investigation aimed to quantify craniofacial variation in a sample of modern humans. In all, 187 consecutive orthodontic patients were collected, of which 79 were male (mean age 13.3, SD 3.7, range 7.5-40.8) and 99 were female (mean age 12.3, SD 1.9, range 8.7-19.1). The male and female subgroups were tested for differences in mean shapes and ontogenetic trajectories, and shape variability was characterized using principal component analysis. The hypothesis of modularity was tested for six different modularity scenarios. The results showed that there were subtle but significant differences in the male and female Procrustes mean shapes. Males were significantly larger. Mild sexual ontogenetic allometric divergence was noted. Principal component analysis indicated that, of the four retained biologically interpretable components, the two most important sources of variability were (i) vertical shape variation (i.e. dolichofacial vs. brachyfacial growth patterns) and (ii) sagittal relationships (maxillary prognatism vs. mandibular retrognathism, and vice versa). The mandible and maxilla were found to constitute one module, independent of the skull base. Additionally, we were able to confirm the presence of an anterior and posterior craniofacial columnar module, separated by the pterygomaxillary plane, as proposed by Enlow. These modules can be further subdivided into four sub-modules, involving the posterior skull base, the ethmomaxillary complex, a pharyngeal module, and the anterior part of the jaws.
Keywords: Adolescent; Adult; Child; Facial Bones; Female; Humans; Male; Regression Analysis; Sex Characteristics; Sex Factors; Skull; Young Adult